If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + -1(2n + -5) = 7 + -3n Reorder the terms: 9 + -1(-5 + 2n) = 7 + -3n 9 + (-5 * -1 + 2n * -1) = 7 + -3n 9 + (5 + -2n) = 7 + -3n Combine like terms: 9 + 5 = 14 14 + -2n = 7 + -3n Solving 14 + -2n = 7 + -3n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '3n' to each side of the equation. 14 + -2n + 3n = 7 + -3n + 3n Combine like terms: -2n + 3n = 1n 14 + 1n = 7 + -3n + 3n Combine like terms: -3n + 3n = 0 14 + 1n = 7 + 0 14 + 1n = 7 Add '-14' to each side of the equation. 14 + -14 + 1n = 7 + -14 Combine like terms: 14 + -14 = 0 0 + 1n = 7 + -14 1n = 7 + -14 Combine like terms: 7 + -14 = -7 1n = -7 Divide each side by '1'. n = -7 Simplifying n = -7
| x*(4*x^2-72*x+308)=0 | | x-1/4=4.33333333 | | 43x-2(13-5x)+7=85 | | 2x^2-8x-64=y | | f(x)=x^5-4x^4+8x^3-12x^2+3x+4.5 | | y+8z=-3y+12z | | 9/10-1/6=5/6-1/6 | | x=y+8z | | x(4x^2-72x+308)=0 | | 4n+3=5n+21 | | -9/4x=36 | | 3x+8=2.5x+12 | | 1x+3y=12z | | -1/9x=7/9 | | 2x-5(3x-6)=123 | | -5r-8=37 | | -2(6x-9)=-34 | | 12(3x-15)+6=1(3x+27)+2x | | 72x^2=72 | | 1/(2m^2)=1/(2m)-1/2 | | 0.05+0.07(100-x)=32 | | 1/2(4x-6)=48 | | x^2+12x+19=4 | | ln(2y+3)=0 | | 0.05+0.07(100*x)=32 | | tan6=2400/x | | 1/(2m^)=1/(2m)-1/2 | | 2x-5=2x+2+x | | x+28+4=3(x+4) | | (y+4)ln(2y+3)=0 | | f(6)+f(x)=4x | | 64=-4(r-5) |